Recovery of Biogas and Other Valuable Bioproducts from Livestock Blood Waste: A Review - Katarzyna Bułkowska; Magdalena Zielińska (Energies)
The anaerobic digestion (AD) of livestock blood represents a sustainable solution for the management of waste generated by the meat processing industry while simultaneously generating renewable energy. The improper treatment of livestock blood, which is rich in organic matter and nutrients, can result in environmental risks such as water pollution, soil degradation, and greenhouse gas emissions. This review examines a range of AD strategies, with a particular focus on technological advances in reactor design, pretreatment, and co-digestion, with the aim of optimizing process efficiency. While the high protein content of blood has the potential to enhance biogas production, challenges such as ammonia inhibition and process instability must be addressed. Innovations such as bio-carriers, thermal pretreatment, and co-digestion with carbon-rich substrates have demonstrated efficacy in addressing these challenges, resulting in stable operation and enhanced methane yields. The advancement of AD technologies is intended to mitigate the environmental impact of livestock blood waste and facilitate the development of a circular bioeconomy. Furthermore, the possibility of utilizing slaughterhouse blood for the recovery of valuable products, including proteins, heme iron, and bioactive peptides, was evaluated with a view to their potential applications in the pharmaceutical and food industries. Furthermore, the potential of utilizing protein-rich blood as a substrate for mixed culture fermentation in volatile fatty acid (VFA) biorefineries was explored, illustrating its viability in biotechnological applications.